Un acercamiento a los bancos de biodiversidad: una alternativa para la inversión en conservación y protección de los recursos naturales - Villanueva Cáceres, Gabriela Alejandra (2022)
Natural resources can be protected through the implementation of different mechanisms. One of these are the biodiversity banks. The latter constitute a private investment measure whose purpose is to help in the conservation of species, habitats, and natural ecosystems. It is worth mentioning that biodiversity banks have been implemented with success in different countries abroad.The present text analyzes what biodiversity banks are and how they work. Then, it explores the way in which these banks have been regulated and incorporated in certain foreign countries. Finally, and most important, the article highlights the main benefits that the implementation of these banks could generate in the Peruvian case.